Spatial Cues Provided by Sound Improve Postural Stabilization: Evidence of a Spatial Auditory Map? - Gandemer, Lennie; Parseihian, Gaetan; Kronland-Martinet, Richard; Bourdin, Christophe (Frontiers in Neuroscience, 2017)
It has long been suggested that sound plays a role in the postural control process. Few studies however have explored sound and posture interactions. The present paper focuses on the specific impact of audition on posture, seeking to determine the attributes of sound that may be useful for postural purposes. We investigated the postural sway of young, healthy blindfolded subjects in two experiments involving different static auditory environments. In the first experiment, we compared effect on sway in a simple environment built from three static sound sources in two different rooms: a normal vs an anechoic room. In the second experiment, the same auditory environment was enriched in various ways, including the ambisonics synthesis of a immersive environment, and subjects stood on two different surfaces: a foam vs a normal surface. The results of both experiments suggest that the spatial cues provided by sound can be used to improve postural stability. The richer the auditory environment, the better this stabilization. We interpret these results by invoking the ’spatial hearing map’ theory: listeners build their own mental representation of their surrounding environment, which provides them with spatial landmarks that help them to better stabilize.